The Influence of Non-Performing Loan and Loan to Deposit Ratio on the Level of Conventional Bank Health in Indonesia - Fajri Hakim (Arthatama, 2017)
This study aims to examine the factors that influence the health of conventional banks in Indonesia. Specifically, this study examined the effect both partially and simultaneously of ratio of non-performing loans (NPL), the ratio of loans to deposits (LDR), good corporate governance (GCG), capital adequacy ratio (CAR), net interest margin (NIM), and operating costs to operating income (OEOI) to the health of conventional banks listed on the Indonesia Stock Exchange. Then, testing is carried out to analyze the factors that have the most dominant influence on the dependent variable of the health bank. This study uses secondary data which includes 20 conventional banks listed on the Indonesia Stock Exchange during the period 2008-2012 using purposive sampling. Data were analyzed using logistic regression to test the effect of independent variables on the dependent variable. The feasibility test of the model and the test of the coefficient of determination are carried out to test the hypothesis with a confidence level of 5%. The results of the study indicate that two independent variables of operating costs to operating income, and good corporate governance have a significant negative effect on the health of the bank. On the other hand, bad credit, the ratio of loans to deposite, net interest margin, and capital adequacy ratio do not significantly influence the health of the bank. Finally, the evidence shows that the predictive power of the logistic regression model is 50.1%. Some implications are discussed at the end of the paper.